2022
DOI: 10.1080/21655979.2022.2061303
|View full text |Cite
|
Sign up to set email alerts
|

Yin Yang 1-stimulated long noncoding RNA bladder cancer-associated transcript 1 upregulation facilitates esophageal carcinoma progression via the microRNA-5590-3p/programmed cell death-ligand 1 pathway

Abstract: Esophageal carcinoma (EC) is a common gastrointestinal malignancy that poses a threat to public health worldwide. Long noncoding RNA (lncRNA) bladder cancer-associated transcript 1 (BLACAT1) exerts a tumorigenic role in several malignant tumors; nevertheless, its function in EC remains largely unknown. Besides, programmed cell death-ligand 1 (PD-L1), an oncogene in numerous human cancers, has been identified as a therapeutic target for EC. Therefore, we intended to explore the potential regulatory network invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Also, BLACAT1 promotes the growth, expansion, and metastasis of esophageal cancer cells by competing with PD-L1 to bind to miR-5590-3p in these cells. Moreover, the study found that silencing PD-L1 partially reversed the promoting effects of BLACAT1 [ 144 ].…”
Section: Micrornas: Bridging the Gap Between Gene Regulation Immune C...mentioning
confidence: 99%
“…Also, BLACAT1 promotes the growth, expansion, and metastasis of esophageal cancer cells by competing with PD-L1 to bind to miR-5590-3p in these cells. Moreover, the study found that silencing PD-L1 partially reversed the promoting effects of BLACAT1 [ 144 ].…”
Section: Micrornas: Bridging the Gap Between Gene Regulation Immune C...mentioning
confidence: 99%
“…in esophageal squamous cell carcinoma, YY1 has been confirmed to bind to the hypomethylation promoter region of ESCCAL-1, [ 54 ] and YY1-induced BLACAT1 was able to compete with PD-L1 for binding to miR-5590-3p in esophageal cancer cells. [ 55 ] FOXP4-AS1 can up-regulate FOXP4 expression and promote the proliferation of esophageal squamous cell carcinoma by sponging miR-3184-5p, and YY1 can promote the activation transcription of FOXP4-AS1. [ 56 ] YY1 promotes the progress of laryngeal squamous cell carcinoma and telomerase activity by inhibiting the stability of GAS5-dependent p53 or reducing the stability of p53 by binding to P300.…”
Section: Yy1 and Lncrnasmentioning
confidence: 99%